Measuring Junior High School Students’ Critical Thinking Skills Through Set Operations Tasks - Nurdalilah, Nurdalilah; Putri, Aziah Aulisa; Siregar, Luthfiyatul Adawiyah; Shaputra, Ramadan; Febrian, Feri Dwi (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
This study aims to describe students’ critical thinking skills. Critical thinking is essential for students, especially in 21st-century learning, where many students use technology to explore answers without fully understanding the questions and the solutions. This study focuses on students’ understanding of set operations in mathematics and identifies the difficulties they face. The participants were 27 ninth-grade students at Al-Manar Junior High School. The study employed a qualitative approach with a descriptive design to analyze students’ abilities to solve problems, decide and implement solution steps, perform operations, and apply mathematical induction related to set operations. The findings are expected to reveal students’ critical thinking skills and their understanding of basic mathematical concepts, particularly in set operations, as well as to identify factors influencing their understanding, thereby improving the quality of mathematics instruction at the primary and secondary education levels. The instrument used to collect data was a test administered to students on the topic of set operations. Data analysis followed these steps: data reduction, data display, and drawing conclusions. The results indicate that students’ ability to solve mathematical problems on set operations is uneven. Based on the critical thinking categories used in this study, no students reached the “very good” category; 80% were in the “good” category, 5% in the “fair” category, and 15% in the “low” category. This distribution was evident in students’ responses, suggesting that their overall problem-solving ability can still be considered good. Therefore, the researcher recommends that teachers pay greater attention to and further develop students’ critical thinking skills and their understanding of basic mathematical concepts.